All-polarization-maintaining linear fiber laser mode-locked by nonlinear polarization evolution with phase bias. (October 2021) - Liu, Guanyu; Ou, Shangming; Zhang, Qingmao; Zhang, Mingsi; Li, Xiangping; Bao, Qiaoliang
Abstract: We report on a novel architecture for robust all polarization-maintaining (PM) femtosecond linear fiber lasers mode-locked by nonlinear polarization evolution (NPE) with phase bias. Due to a non-reciprocal phase shift, the reflectivity of the artificial saturable absorber has a steeper slope around zero difference in nonlinear phase shift between the orthogonal polarizations, offering the possibility to reduce mode locking threshold and reach high repetition rates. We demonstrate an environmentally stable self-starting 105 MHz repetition rate linear Yb:fiber laser based on NPE with phase bias mode locking. The laser delivers an average power of 26.3 mW and 332 fs pulse which is further compressed to 91 fs at a pump power of 425 mW. Our work provides a novel promising compact and robust femtosecond laser for ultrafast photonic applications.